Measurement of the flux-weighted average cross section for the \(^{186}\)W\((γ,p)^{185}\)Ta reaction at the bremsstrahlung end-point energy of 70 MeV - Do, Nguyen Van; Tran, Dinh Trong; Kim, Tien Thanh; Nguyen, Thi Hien; Kim, Guinyun; Bui, Thi Hoa (Communications in Physics, 2023)
Abstract. The flux-weighted average cross section for the 186W(γ,p)185Ta reaction induced with 70 MeV bremsstrahlung end-point energy was measured using the activation method in combination with off-line gamma activity measurement. The 27Al(γ,2pn)24Na monitor reaction was used for the determination of the bremsstrahlung flux. The bremsstrahlung photons used to produce the photonuclear reactions were generated from a thin tungsten (W) converter by bombardment with a 70 MeV electron beam. The experimental flux-weighted average cross section is compared with the theoretical prediction, for which the absolute cross section was calculated using the TALYS 1.95 code and the bremsstrahlung spectrum was simulated using the computer program MCNPX. The present experiment was carried out at the 100 MeV electron linac of the Pohang Accelerator Laboratory, POSTECH, Pohang, Korea.